Matrisome remodeling in the myocardium of hypertrophic cardiomyopathy; novel targets for molecular diagnostics - Ibrahim, Ayman M.; Elfawy, Hasnaa A.; Terracciano, Cesare M.; Yacoub, Magdi (Frontiers in Cell and Developmental Biology, 2025)
Hypertrophic cardiomyopathy (HCM) is an inherited cardiac disorder characterized by left ventricular thickening and extracellular matrix (ECM) remodeling, often manifested as increased interstitial fibrosis that impair muscle function. The clinical and pathological presentations, as well as the genetic background, vary among patients, making HCM a heterogeneous disease with diverse clinical phenotyping and responses to treatment. In HCM, the myocardium exhibits an increased secretion of inflammatory mediators and ECM proteins, indicating a stress response to myocardial pathogenesis. The production of these ECM proteins is regulated by the interaction between cardiomyocytes and the surrounding stroma, including cardiac fibroblasts, immune cells, and microvasculature. This crosstalk defines the responsiveness to injury and the progression of the disease. In this review, we aim to dissect the composition of myocardial ECM in relation to HCM development, highlighting the key cellular contributions to ECM remodeling and identifying potential molecular targets for personalized diagnostics and therapeutics.